The Uniqueness of Kampung Naga as A Cultural Tourism Attraction in Kabupaten Tasikmalaya - Hamzah, Faizal (Media Wisata, 2023)
Kampung Naga is a Traditional Village located in Tasikmalaya Regency, which still runs life guided by the legacy of its predecessors. Kampung Naga has its uniqueness. Unique here means having something distinctive. One of the uniqueness of Kampung Naga is in Norma, life habits, arts and religious rituals. This study aims to discover the unique form of Naga village and how this uniqueness can become a cultural tourism attraction. The research method used is a qualitative method with a descriptive study approach. The source of research data consists of Primary data obtained through Interviews and Observations, while secondary data can be through literature studies and; for the results of this study is the Uniqueness of Kampung Naga as a Cultural Tourism Attraction in Tasikmalaya Regency.